2009
DOI: 10.2215/cjn.01510209
|View full text |Cite
|
Sign up to set email alerts
|

Dystroglycan in the Diagnosis of FSGS

Abstract: Background and objectives: ␣-and ␤-dystroglycan (DG), which link the actin cytoskeleton of the podocyte to the glomerular basement membrane, are maintained in FSGS but decreased in minimal change disease (MCD). Fibrosis has been linked to increased fibroblast-specific protein-1 (FSP1) and epithelial-mesenchymal transition. We studied DG, FSP1, and podocyte differentiation in FSGS variants and cases of suspected FSGS.Design, setting, participants, & measurements: We studied renal biopsies with FSGS, not otherwi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
27
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…These efforts are to improve the diagnosis and subsequent treatment of the diseases and to obtain a better understanding of the pathomechanisms of both diseases. It was proposed that differences in the podocyte expression of dystroglycans could discriminate between MCD and FSGS because only in MCD the expression of b-dystroglycan 24 and a-dystroglycan 25 was reduced. This would also suggest that the pathomechanism underlying MCD may be different from that of FSGS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These efforts are to improve the diagnosis and subsequent treatment of the diseases and to obtain a better understanding of the pathomechanisms of both diseases. It was proposed that differences in the podocyte expression of dystroglycans could discriminate between MCD and FSGS because only in MCD the expression of b-dystroglycan 24 and a-dystroglycan 25 was reduced. This would also suggest that the pathomechanism underlying MCD may be different from that of FSGS.…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies have been debated because the findings in later studies by the same group 26 and other groups 27,28 were not consistent with the previous studies. 24,25 More recently it was found that urinary soluble CD80 (B7.1) is elevated in MCD and not in FSGS, which could be promising for both diagnosis and pathogenesis of the disease. 29 To discriminate MCD from FSGS, we focused on the role of PECs in the development and progression of FSGS.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they found that in minimal-change nephropathy (MCN), protein expression was reduced by 75% for ␣-dystroglycan and by 50% for ␤-dystroglycan, whereas expression of both dystroglcyans was normal or slightly increased in FSGS. In this issue of CJASN, Giannico et al (2) extend these findings to a somewhat different clinical setting, namely, seven patients with findings typical of MCN, including extensive foot process effacement and nephrotic proteinuria (with the exception that one patient had subnephrotic proteinuria). Because of limitations in the number of glomeruli present on these biopsies, the diagnosis of unsampled FSGS could not be safely excluded, and this group is therefore described as "undefined."…”
mentioning
confidence: 90%
“…It is also possible that dystroglycan gene expression will add useful information, perhaps assessed as part of a molecular profiling approach, as has been described by Kretzler and colleagues (14). A fairly common clinical dilemma, similar to that studied by Giannico et al (2), is a renal biopsy obtained from a patient with nephrotic range proteinuria that manifests nondiagnostic abnormalities such as focal global glomerulosclerosis and/or focal tubular atrophy, interstitial inflammation, or interstitial fibrosis. Does this individual have MCN, or does this the patient have FSGS, unsampled because of the limitations of the biopsy sample?…”
mentioning
confidence: 98%
See 1 more Smart Citation